Avaliação de projetos de investimento em TI utilizando opções reais: aplicações no setor de indústrias alimentícias no estado do Ceará - Correia Neto, Jocildo Figueiredo (2010)
There are some ways to perceive the relevance of information technology (IT) in companies. One of these ways is through the high volumes of financial resources invested in IT projects. Besides, there are many evidences indicating a growing tendency in IT capital budget. This scenery can lead to a discussion about the methods utilized to justify these investments, considering the several kinds of expected benefits and involved risks. Besides, certain projects can incorporate characteristics like managerial flexibility in order to take advantages in positive situations and avoid negative situations, possibility of future opportunities creation and analysis and execution in stages. In this circumstance, these projects can be evaluated through real options approach, which recognizes and assesses the added value due to contingent decisions that can be taken thorough the life time of project, providing a dynamic perspective to the valuation. The goal of this research is to verify if, in fact, IT projects can be evaluated through real options approach and under which circumstances this can be done. So, it was conducted a bibliographic revision about IT investments characteristics. After this, elements observed in valuations were researched, like project classification, expected returns, involved risks and valuation methods. Further, the object of study was real options analysis, with emphasis in the circumstances that indicate their use and their major concepts. An empirical research was conducted in the food industry sector, specifically with the greatest companies located in Ceará State. The predominant methodology was qualitative, using surveys to collect some descriptive data and interviews to collect the core information. The IT management responsible executives participate of this research, providing data about the IT projects characteristics and how they are actually evaluated. The research showed a number of examples of projects analyzed in companies that incorporated real options. There was a predominance of expansion and delaying options in the projects, while there was no evidence of abandonment and contraction options. The research also showed that, in some cases, the real options method could have been used in decision-making to justify the investments. Although none of the researched companies apply explicitly the real options method, it was perceived that the options concepts are used informally. This indicates the possibility of incorporating the method in cases where projects have features for a contingency 9 and opportunities, that is, those of strategic nature. The research concluded that the use of real options approach, measuring the value added generated by the existing options in the projects, can make decision making on IT investments clearer and more objective than just intuitively use the options thinking.